Avgustin’s version of universalize the concept of peace as a principle of harmonization immanent and transcendental - Turenko, Oleh (Skhid, 2014)
The article deals with the concept of peace in the Holy imagined. Augustine - the value of this concept for a positive solution to the problem of synchronization of collective and individual and maintaining communication between the immanent and transcendent. It is concluded that the concept of peace in Augustine’s Christian doctrine was universal meaning through its complexity and cumulativeness towards approaching the ordo amoris and salvation - a practical movement immanent to the transcendent, and vice versa. Father of the Church interpreted peace like a multilayer condition of united harmony - unanimity individual and collective. Due to individual achievement of peace at all levels of social, political and religious life pax aeterna pax sempiterna and most are near and so bring humanity to God’s grace. The point spread peace was both individual and collective responsibility, religious and moral virtues of true believers - all Respublica Christiana. Guide this case should lead the Church, which is part of the sacred nature is in pax aeterna, and so brings pax sempiterna to His plan. So peace in Avgustin’s theory provides harmony and positive movement immanent to the transcendent, synchronizes broken individual sinfulness of collective harmony and provides a certain level of freedom that aims at implementing free will. No doubt Augustinian concept of peace has played in the Middle Ages and early modern key role in the development of humanity and the formation of European principles of coexistence of peoples and nations. Avgustin’s doctrine of peace through practical pax Dei (they promoted the Church in the tenth to thirteenth centuries. Pacification for feudal wars and legitimized royal authority), the creative heritage of Dante and Marsyliya Padua became the foundation of modern political philosophy and the key to the future of European civilization.